Czym jest dziś czytanie literatury? Ankieta - Sosnowski, Jerzy (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The writer shares his personal literary preferences and choices, discussing how the books he was reading in his childhood and youth influenced his later understanding of literature. He talks about the most important books of his life and ones to which he returns in search of ever new meanings and emotions. He reveals why depressing works can chase away the blues, and detective novels are a good choice for when you are tired. Finally, he explains what Joanna Chmielewska and Henryk Sienkiewicz have in common...